Does biofilm origin matter? Biofilm responses to non‐flow period in permanent and temporary streams. (15th December 2019) - Timoner, Xisca; Colls, Miriam; Salomón, Samia M.; Oliva, Francesc; Acuña, Vicenç; Sabater, Sergi
Abstract: In some regions, climate change is increasing the variability of rainfall and the frequency of extreme events such as drought. Consequently, non‐flow periods have grown in length and frequency, both in temporary and in formerly permanent streams. Water abstraction for human use may further prolong these dry periods. We analysed the resistance and resilience of biofilms from permanent and temporary streams to non‐flow conditions. This was achieved by exposing cobbles (collected from permanent and temporary streams) with intact biofilm to 31 days of non‐flow, followed by 20 days of stream flow in artificial stream channels. Biofilm resistance and resilience were assessed at a structural (algal biomass, pigment composition, and algae and cyanobacteria composition) and functional level (photosynthetic efficiency and community metabolism). Algal taxa in biofilms from permanent and temporary streams differed throughout the experiment. Biofilms from permanent streams were less resistant to non‐flow than those from temporary streams at structural level. Permanent stream biofilms also presented lower resilience at a structural level, but responded similarly to temporary stream biofilms at a functional level. Our investigation shows how the non‐flow period disturbed permanent stream biofilms, and suggests that temporary stream biofilms will have greater adaptive capacity as hydroperiod becomes shorter due to climate change.